Identification of Students' Metacognitive Levels in Physics Learning Viewed from the Problem-Solving Ability. (February 2020) - Yuberti,; Kartika, I; Viyanti,; Wulandari, H; Anillah,
Abstract: This study aimed to look at the level of physics problem-solving ability achieved by students and identify the level of metacognition based on the ability to solve physics problems at each level. The research method used was a mixed method with a sequential explanatory strategy. The populations in this study were all eleventh-grade science students of Kebumen Islamic High School, Tanggamus District. The sampling technique used was a balanced sample with a participant selection model. The instruments used in this study were the physics tests, interviews, and documentation. The data analysis process included two stages of analysis, namely quantitative data analysis and qualitative data analysis. The results of this study indicated that 12.12% of students belong to the high problem-solving group, 66.67% of students belong to the moderate problem-solving group, and 21.21% of students belong to the low problem-solving group. The high problem-solving group had a high level of metacognition, namely Semi-reflective use with a percentage of 10% and Strategic use with a percentage of 10%. The moderate problem-solving group had Semi-strategic use level with a percentage of 40% and Aware use with a percentage of 20%. The low problem-solving group had the lowest metacognition level, namely Tacit use with a percentage of 20% of the total sample taken. so, the levels of metacognition ability of students in learning physics identified in this study were: tacit use, aware use, semi strategic use, strategic use, and semi-reflective use.